منهجية الإمام محمد أبي زهرة في توضيح أصول النصرانية تاريخا وعقيدة : تحليل ونقد - عبد المولى، عبد الرحمن بهاء الدين
This study deals with the methodology of Imam Muhammad Abu Zuhrah in clarifying and explaining in detail the fundamental tenets of Christianity and the historical stages he went through. It is done by analyzing his writings and critiquing them as needed. The study reveals the cultural and religious circumstances in which he lived, explaining the relations between Muslims and Coptic Christians at the time. The study also substantiates the debate between Islam and Christianity throughout history, the arguments of leading Muslim scholars against Christianity, and Abu Zahrah's stature among scholars who participated in this debate. It clarifies Abu Zahrah's methodology in dealing with Christian tenets in the light of the relevant Qur'anic verses and ascertains its objectives and the scholarly methodology that Abu Zahrah adhered to in studying, explaining and analyzing the fundamental tenets of Christianity. It also explains the numerous and varied scholarly methodologies Muslim scholars of the past and the present have adhered to and the particular methodological, scholarly and intellectual characteristics that distinguish them. This study used an aggregative inductive methodology by tracing Abu Zahrah's writings on Christianity in their original sources. It has also made use of a descriptive and analytical methodology in discussing the Christian texts cited by Imam Abu Zahrah. Included is the historical methodology in tracing the historical stages undergone by the Christian creed. The researcher arrives at the following conclusions from the research: the Islamic creed is constant, stable and unchanging, as it is revelation sent down by Allah to the seal of the prophets and messengers, Muhammad (peace be upon him). Thus, it is not subject to personal whims or human negotiation. The researcher also concludes that it is necessary to revisit and examine in detail Imam Abu Zahrah's thoughts and his most important opinions for they comprise an exemplary model in the field of comparative religion. Academics, thinkers and preachers can all benefit from the rich intellectual, academic and invitational legacy left by him.